Pelaksanaan Ronde Keperawatan Terhadap Tingkat Kepuasan Kerja Perawat di Ruang Rawat Inap RSI Ibnu Sina Padang Tahun 2022 - Ananda, Yuanita; Putri, Zifriyanthi Minanda; Muliantino, Mulyanti Roberto; Muthmainnah, Muthmainnah; Nelwati, Nelwati; Gusdiansyah, Edo (REAL in Nursing Journal, 2022)
Background: Nursing services are often used as a benchmark for the image and quality of a hospital in the eyes of the community. One indicator of improving the quality of service is job satisfaction of nurses. Nursing round is one of the activities that can increase nurse job satisfaction. This study aims to identify the effect of the implementation of the nursing round on the job satisfaction of implementing nurses in the inpatient ward. Methods: This type of research uses a pre-experimental design with the One Group Pretest-Postest Design which was carried out in May-July 2022 with a population of all nurses in the inpatient room of RSI Ibnu Sina Padang with a sample size of 30 respondents. Instruments in this study in the form of questionnaires and observation sheets. Results: The results showed that there was a significant effect of the nursing round on the level of job satisfaction of nurses in the inpatient room with a p-value of 0.022 (p <0.05). There was a significant difference in the level of job satisfaction of nurses before and after the nursing round (p < 0.05). Conclusion: It is hoped that hospital management will measure the job satisfaction of implementing nurses and develop policies related to the implementation of the nursing round.